PELATIHAN KEWIRAUSAHAAN “KERUPUK TULANG IKAN” DI DESA PADANGBANDUNG GRESIK (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
This training was carried out against the background of the abundance of milk thorn waste that was thrown away. This training aims to provide knowledge to the community in entrepreneurship and provide knowledge on the use of milkfish spines. This training was attended by every citizen of Padangbandung Village. The results showed that the enthusiasm of the residents of Padangbandung Village was very good and the community was satisfied with the material presented.